Rancang Bangun Sistem Monitoring Kualitas Air dan Stasiun Cuaca Berbasis Sensor Industrial dengan Protokol Modbus RS485 - Prakasa, Aras Teguh; Liyantono; Widodo, Slamet; Fatikhunnada, Alvin Fatikhunnada (PERTETA, 2025)
River water quality is typically monitored using sampling methods. This approach makes detecting water pollution challenging owing to the limited sampling time. Another factor influencing water quality is weather, which can be addressed by incorporating weather station sensors as corrective tools. The collected data were processed and visually displayed to make the important information easily interpretable. The water quality parameters measured in this study included Electrical Conductivity (EC), temperature, Total Dissolved Solids (TDS), salinity, pH, turbidity, Dissolved Oxygen (DO), and saturation. The weather parameters measured by the system included wind speed, wind direction, air temperature and humidity, atmospheric pressure, rainfall, and solar radiation. The system's capabilities include data transmission via cellular networks, data backup using an SD card, and industrial sensors with IP (Ingress Protection) standards that utilize the Modbus RS485 protocol. The study followed the Software Development Life Cycle (SDLC) or waterfall method to ensure system readiness and durability in real-world environments. The Modbus RS485 protocol allows multiple sensors to share a single cable line, resulting in a more efficient and less complex wire arrangement. These findings highlight the necessity of separating sensor lines based on parity type and baud rate for each sensor, enabling simultaneous readings in subsequent operations.